A prospective study on emergence of mucormycosis in recently recovered COVID-19 patients - Landge, Suvarna; Menon, Sarala; Chande, Chhaya; Kulkarni, Monita; Bhilkar, Kavita; Bade, Jyoti; Joshi, Ameeta (International Journal of Research in Medical Sciences, 2023)
Background: Mucormycosis is an angio-invasive fungal infection with high morbidity and mortality. This infection seems to be increasing during the second wave of COVID-19. Objectives of this study were to identify and characterise the fungal species causing post-covid-mycosis, to analyze the cases for underlying co-morbidities if any and to correlate the associated risk factors with the progression of disease. Methods: Prospective observational study which constituted conventional fungal culture of 188 tissue specimens collected from clinically suspected mucormycosis patients who had history of COVID. Results: This study noted the occurrence of disease with predominance of males (72.03%). Most common symptoms were facial/periorbital swelling, followed by facial pain and headache. Among co-morbid conditions, diabetes mellitus was the most common (71.17%). Use of steroids (65.25%), antivirals therapy (22.86%), oxygen support (11.86%) used in management of COVID patients were found to be risk factors in post-covid-mucormycosis. radiological diagnosis showed involvement of paranasal sinuses (77.11%), followed by orbit (16.94%) and brain (5.90%). Mucor spp. was isolated in 21 cases. Although commonest fungus isolated was Aspergillus, analysis of the data for last 5 years showed a significant rise of Mucormycosis cases. Mortality was seen in 17.79% cases. Conclusions: Fungal aetiology should be kept in mind in patients with above clinical presentations with history of recent COVID-19 infection especially who received steroids.